An improved PCR method for detection of HIV-1 proviral DNA of a wide range of subtypes and recombinant forms circulating globally (2011)
Proviral DNAs are being measured increasingly as a marker of the efficacy of highly active anti-retroviral therapy (HAART) and is accepted for the early diagnosis of perinatal HIV-1 infections. This requires a standardized test which enables the detection of a wide range of subtypes worldwide including O, N and circulating recombinant forms (CRFs). Based on a previous publication, a PCR - Test for HIV-1 provirus detection in peripheral blood mononuclear cells (PBMCs) was developed. Blood samples from 80 individuals infected with HIV-1 and 20 persons negative for HIV-1&2 from Africa and Germany were tested for the presence of HIV-1 provirus DNA. The primer system used enables the detection of proviral DNA despite the high concentrations of human DNA. The limit of detection was determined to be 5 copies per 10(5) cells. All 20 samples from persons negative for HIV were negative for HIV-1 proviral DNA while provirus DNA was amplified from 76 of the 80 (95%) samples from persons infected with HIV. The amplified products were detected by gel-electrophoresis, flow cytometry and real-time PCR. All three detection systems provided the same results.